Attitudes and Motivations for Code Switching among Mozabite Speakers in Ghardaia: A Sociolinguistic Study (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Abstract: The Paper Is A Sociolinguistic Study Of Code Switching Among Mozabite Speakers In Ghardaia. It Examines The Language Choice Of Mozabite Speakers Within Different Domains, In Addition To Their Motivations And Attitudes Towards The Use Of Code Switching. To Reach The Objectives Of The Study, An Online Questionnaire Consists Of Five-Point Likert Scale Is Distributed To 235 Random Participants. The Data Analyzed Shows That The Vast Majority Of The Participants Predominantly Use Their Mother Tongue (Mzabi) At Home, With Family Members And When Discussing Personal Matters. However, They Tend To Mix Arabic And French With Mzabi Most Of The Time Outside Their Home, With Friends And When Discussing Business Matters. The Findings Also Show That The Respondents’ Motivations For Code Switching Range From The Lack Of Equivalents In Their Native Language, The Establishment Of Solidarity And Common Identity And The Need Of Feeling Confident In Addition To The Attraction Of Listeners’ Attention. Finally, The Results Of The Questionnaire Show That Mozabite Speakers Hold Positive Attitudes Towards The Use Of Code Switching.  Keywords: Sociolinguistics, Code Switching, Motivations, Attitudes, Mzabi, Arabic, French.